Desafios e limites do controle judicial no acordo de não persecução penal: uma análise das implicações constitucionais e procedimentais - Silva, Francisco de Assis Santos da (2025)
The judicial system is overwhelmed with cases that take years to be judged. The prison system contains people who have not been tried and are waiting for the results of these cases, as well as those who have already been tried and are serving their sentences, which also number in the thousands. Thus, a consensual institution, such as the Non Prosecution Agreement (ANPP), established in 2019 by Law No. 13,964, which inserted article 28-A into the Penal Code, can help to solve both problems. In the ANPP, the Public Prosecutor's Office has primacy in the negotiations and the judge only approves the agreement, verifying its legality, the defendant's willingness to make a mandatory confession, and the fairness and equity of the process. In view of this, many criticisms are made, arguing that the judge could have a more assertive role, participating in the negotiations and also monitoring compliance with the agreement. The objective of this study was to analyze the limits and challenges of judicial control in the ANPP, in light of Law 13.964/2019, focusing on how the role of the judge as a mere ratifier impacts the guarantee of constitutional rights, especially with regard to confession and non-violation of the fundamental rights of the person under investigation. This is a bibliographic review, which sought to gather the works of scholars who expressed their opinions, whether favorable or contrary, to the way in which judicial control was established in the ANPP and what the legislation on which it is based states. The study was divided into three chapters. After analyzing the material presented by the consulted scholars, as well as legislation and case law, it was concluded that the ANPP represents an advance in the Brazilian judicial system, resolving minor crimes more quickly and without imprisoning those who committed them. However, judicial control could be broader, verifying the adequacy of the conditions imposed at the very moment they are negotiated, to avoid breaches of rights and injustices. The actions of the Public Prosecutor's Office, in offering or not offering the ANPP, as well as the conditions under which the technical defense is carried out, should also be subject to judicial control, to avoid arbitrariness and omissions, respectively. Thus, increased judicial control over the ANPP would serve to guarantee the fairness and transparency of this legal transaction that brings benefits to the Brazilian justice system.